Anti-corrosive properties of Poly(aniline-co-2, 3-xylidine)/ZnO nanocomposite coating on low-carbon steel. Issue 7 (3rd April 2017) - Mobin, Mohammad; Aslam, Jeenat; Alam, Ruman
Abstract: A copolymer nanocomposite Poly(aniline-co-2, 3-xylidine)/ZnO [Poly(AN-co-XY)/ZnO], pure copolymer and its homopolymers namely, Poly(aniline-co-2, 3-xylidine) [Poly(AN-co-XY)], Polyaniline (PANi) and Poly (2, 3-xylidine) were synthesized by chemical oxidative polymerization using ammonium persulfate as an oxidant in hydrochloric acid medium. The synthesized compounds were characterized by FTIR, XRD, SEM, and TEM techniques. Saturated solutions of the synthesized compounds were made in N-methyl-2-pyrrolidone and casted on low-carbon steel specimens using 10% epoxy resin as a binder. The anticorrosion behavior of polymeric coatings was studied in 3.5 wt% NaCl solution at a temperature of 30 °C by electrochemical techniques, which include: open-circuit potential, potentiodynamic polarization and electrochemical impedance spectroscopy. Protective properties of nanocomposite coating were also evaluated at different immersion times for an extended period of 60 days. Anticorrosion properties of nanocomposite coating were compared with parent copolymer and individual homoplymers. SEM photomicrographs of the coated surface showed that Poly(AN-co-XY)/ZnO nanocomposite coating is crack free, uniform, and compact, whereas, copolymer and homopolymer coatings have surface defects. The performance of the polymer coatings followed the order: Poly(AN-co-XY)/ZnO > Poly(AN-co-XY) > PANi > Poly(2, 3-xylidine). The presence of ZnO nanoparticles in copolymer resulted in significant improvement in corrosion resistance and provided better barrier properties.